Chill-inducing music enhances altruism in humans - Fukui, Hajime; Toyoshima, Kumiko (Frontiers in Psychology, 2014)
Music is a universal feature of human cultures, and it has both fascinated and troubled many researchers. In this paper we show through the Dictator Game that an individual’s listening to preferred “chill-inducing” music may promote altruistic behavior that extends beyond the bounds of kin selection or reciprocal altruism. Participants were 22 undergraduate and postgraduate students who were divided into two groups, the In-group (IG) and the Out-group (OG), and they acted as dictators. The dictators listened to their own preferred “chill-inducing” music, to music they disliked, or to silence, and then played the Dictator Game. In this hypothetical experiment, the dictators were given real money (which they did not keep) and were asked to distribute it to the recipients, who were presented as stylized images of men and women displayed on a computer screen. The dictators played the Dictator Game both before and after listening to the music. Both male and female dictators gave more money after listening to their preferred music and less after listening to the music they disliked, whereas silence had no effect on the allocated amounts. The group to which the recipient belonged did not influence these trends. The results suggest that listening to preferred “chill-inducing” music promotes altruistic behavior.